Uma análise dos impactos do agronegócio para os assentamentos poço Tilon, Cruzeiro e Frei Damião (Apodi-RN/ (2016-2019) - Costa, Ana Claudia de Andrade (Universidade Federal Rural do Semi-Árido, 2020)
The practice of agriculture has changed nature. Relations between the environment and people have been constantly changing, notably from the process known as the “modernization of agriculture”. Therefore, this study aims to investigate: What are the implications of the expansion of agribusiness for the rural communities of Poço de Tilon, Frei Damião and Cruzeiro located in the municipality of Apodi-RN? As a result, our specific objectives aim to analyze: (A) to identify the profile of companies and areas occupied by the cultivation of irrigated fruit in the rural communities of the Chapada do Apodi-RN; (B) to analyze the labor relations of young women and men who work in irrigated fruit companies in the Apodi-RN region; (C) investigate the presence of women in companies and the impacts on the health of people involved in agribusiness In order to achieve the objectives of the research, we performed a bibliographic review, seeking to dialogue with some authors, such as Raquel Rigotto (2016) from from which we discussed the concepts of environment and health of the peasant population; Fleury (2010), which enabled us to understand the concept of work relationships in the field; Delgado (2012) who analyzes the counter hegemony of agribusiness in the countryside; Richardson (1999), Eckert and Rocha (2007) who contributed to the understanding of the qualitative research method and how to proceed with the field research. Methodologically, we applied questionnaires to residents of the community and conducted semi-structured interviews with employees and former employees of the irrigated fruit companies. Then the data were tabulated for the construction of the final work. With our results, we can see that there was degradation of the environment with the actions of irrigated fruit companies, changes in the dynamics of social and work relations, negatively influencing the health of workers and residents of the region due to direct contact with pesticides. We conclude that, although companies interfere in the national and local economy, their presence has caused serious problems for the communities in which they are located and, consequently, for peasant populations
Keywords: Agronegócio; Fruticultura irrigada; Relações de trabalho; Oeste potiguar; Agribusiness; Irrigated fruit growing; Work relationships; West potiguar; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES